Microbe - Schaechter, Moselio; Ingraham, John L.; Neidhardt, Frederick C. [ (Frederick Carl] , 1931-2016 (American Society for Microbiology, 2006)
Microbe, a brand-new, general microbiology textbook intended for upper-division undergraduate and beginning graduate courses, is an exciting introduction to the world of microbes